2018
DOI: 10.1507/endocrj.ej17-0253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum ferritin and thyroid function in the second trimester of pregnancy

Abstract: Abstract. Ferritin is a universal intracellular protein that acts as an iron carrier. Several studies have indicated that iron deficiency affects thyroid function in non-pregnant women. Our objective was to assess the relationship between serum ferritin levels and thyroid function in pregnant women during the second trimester. Pregnant women with sufficient iodine intake and normal antithyroid antibodies during the second trimester were recruited from the obstetric outpatient department of the Fifth People's H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Sixteen of them were downloaded in full and read carefully. Eight articles were excluded because the data couldn't be extracted (20,21) or the research subjects were not grouped according to ID (10,(22)(23)(24)(25)(26). Finally, a total of eight articles were included in our meta-analysis ( Figure 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen of them were downloaded in full and read carefully. Eight articles were excluded because the data couldn't be extracted (20,21) or the research subjects were not grouped according to ID (10,(22)(23)(24)(25)(26). Finally, a total of eight articles were included in our meta-analysis ( Figure 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Iron is an important micronutrient for maintaining cell energy and metabolism (8). Iron deficiency (ID) manifested as a decrease in the extracellular iron of the bone marrow and lower serum ferritin than normal, is concerned as the most common nutritional deficiency worldwide and can lead to adverse effects on thyroid metabolism in both reproductive-age women and pregnant women (9,10). Some studies have shown that ID can negatively impact thyroid function by interfering with oxygen transport or affecting thyroid peroxidase activity (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, iron deficiency is often linked to thyroid diseases, as less iron reduces the activity of thyroid peroxidase -an enzyme essential for the production of thyroid hormones. Concluding, in pregnant women a complete blood count should be monitored, and in case of anaemia, diagnostics directed towards thyroid diseases should be initiated, even if they were not diagnosed before pregnancy [8]. Keskin et al described differences in haematological parameters between patients with Hashimoto's thyroiditis and a healthy control group, both being euthyroid [9].…”
Section: Reviewmentioning
confidence: 99%
“…Iron nutrition has a profound influence on brain development and neurotransmitter formation during fetal development. The most striking effect of ID is the impairment of intellectual function 4 . ID can disrupt the brain development and lead to abnormal hippocampal structure and function; it also changes brain energy metabolism and neuronal signaling [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%